Improving Students’ Writing Skill using Collaborative Instructional Strategy - Rafika Amalia (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2020)
ABSTRACT The objective of this research was to find out the effect of collaborative instructional strategy on students' writing skill in English essay writing. This research was quantitative research using quasi experimental design. The population of the research was the entire class of tenth grade students of SMAN 14 Kota Tangerang. The subjects of the research were class X MIA 2 (experimental class) and X MIA 3 (control class) with nonequivalent control group design where the control group and experimental group were not chosen randomly. The experimental class was stimulated by using collaborative instructional strategy and the control class was using conventional method. The instrument used was pre-test and post-test. In the test of hypothesis, it was obtained that tcount was 6.779 after being consulted with the ttable at the significant level Â = 0.05 and the degree of freedom was 58, it was obtained that the ttable was 1.672. Finally, it was indicated that hypothesis Ho is rejected and Ha is accepted because the tcount is higher than the ttable. Therefore, it can be concluded that there is a significant effect of collaborative instructional strategy on students' writing skill in essay writing.